2021
DOI: 10.1080/1331677x.2021.1931909
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the impact of intellectual property protection and spillovers on attracting foreign direct investment

Abstract: Previous studies yield ambiguous results from using country-level indices of intellectual property rights (I.P.R.) protections to test their relation to foreign direct investment (F.D.I.). This study develops a simple model featuring vertically linked stages of production to show that country-level I.P.R. indices might cause the ambiguity by ignoring differences in I.P.R. protection strength across industries. We demonstrate that industry-level I.P.R. indices resolve ambiguity over the empirical nexus between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Awokuse and Yin (2010) identified a positive relationship between INPR and FDI in a study of China; Blyde and Acea (2002) found the same result in a study of the Organisation for Economic Co-operation and Development (OECD) countries after considering the moderating effects of infrastructure and human capital levels. Such studies indicate that INPR affects the industry and composition of FDI; however, the analysis has tended to focus on foreign investment evidence rather than the development of countries or their technical capabilities classified by industry (Chen, 2021a). Finally, Park and Lippoldt (2003) found a positive effect between INPR and outward FDI due to the organisation of INPR reforms.…”
Section: Empirical Evidence About Intellectual Property Rights and Fo...mentioning
confidence: 99%
“…Awokuse and Yin (2010) identified a positive relationship between INPR and FDI in a study of China; Blyde and Acea (2002) found the same result in a study of the Organisation for Economic Co-operation and Development (OECD) countries after considering the moderating effects of infrastructure and human capital levels. Such studies indicate that INPR affects the industry and composition of FDI; however, the analysis has tended to focus on foreign investment evidence rather than the development of countries or their technical capabilities classified by industry (Chen, 2021a). Finally, Park and Lippoldt (2003) found a positive effect between INPR and outward FDI due to the organisation of INPR reforms.…”
Section: Empirical Evidence About Intellectual Property Rights and Fo...mentioning
confidence: 99%